Perlindungan Hukum Bagi Pengguna Rokok Elektrik: Perspektif Hukum Kesehatan - Yolanda Assyar; Hilman Nur; Aji Mulyana; Trini Handayani (Indonesian Journal of Law and Justice, 2025)
The phenomenon of smoking has become a habit for society. In fact, this smoking habit is difficult to break and is rarely recognised by people as a bad habit. Control of conventional cigarettes and electronic cigarettes, in Indonesia, is very urgent. In this study the author focuses on legal protection for e-cigarette users reviewed based on WHO policy and Law Number 17 of 2023 concerning Health. The research method uses qualitative and document study data collection techniques, as well as a normative juridical approach method. The results showed that legal protection for e-cigarette users from the health aspect through efforts by the government which includes repressive and preventive protection. With the reinforcement through Law No. 17 of 2023 concerning Health and PP No. 28 of 2024 concerning Regulations on the Implementation of the Law on health which regulates the sale and restriction of cigarette advertising, as well as health warnings for cigarette users. The impact of e-cigarette use on health can trigger various diseases such as cancer, affect oral health, brain development, and respiratory disorders. Health protection strategies are realised through regulations issued by the government. The strategy to overcome the use of e-cigarettes in accordance with WHO policy and the Health Law requires cooperation from various parties, not only the government.